Disentangling the Effect of Valence and Arousal on Judgments Concerning Moral Transgressions. (10th August 2015) - de la Viña, Luis; Garcia-Burgos, David; Okan, Yasmina; Cándido, Antonio; González, Felisa
Abstract: An increasing body of research has investigated the effect of emotions on judgments concerning moral transgressions. Yet, few studies have controlled for arousal levels associated with the emotions. High arousal may affect moral processing by triggering attention to salient features of transgressions, independently of valence. Therefore previously documented differences in effects of negative and positive emotions may have been confounded by differences in arousal. We conducted two studies to shed light on this issue. In Study 1 we developed a questionnaire including vignettes selected on the basis of psychometrical properties (i.e., mean ratings of the actions and variability). This questionnaire was administered to participants in Study 2, after presenting them with selected pictures inducing different valence but equivalent levels of arousal. Negative pictures led to more severe moral judgments than neutral ( p = .054, d = 0.60) and positive pictures ( p = .002, d = 1.02), for vignettes that were not associated with extreme judgments. In contrast, positive pictures did not reliably affect judgments concerning such vignettes. These findings suggest that the observed effects of emotions cannot be accounted for by an increase in attention linked to the arousal which accompanies these emotions.